Optimalisasi Peran Auditor Internal dalam Pencegahan Kecurangan: Budaya Lokal sebagai Variabel Moderasi - Usman Usman (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
This study investigates the effect of optimizing the role of internal auditors on fraud prevention by considering local culture as a moderating variable. This study aims to analyze the effect of optimizing the role of internal auditors on fraud prevention with local culture as a moderating variable. Sampling using purposive sampling, this study involved 87 auditors from the regional Inspectorate, with data collection through questionnaires analyzed using the PLS-SEM method and SmartPLS software version 4. The results of the study indicate that the role of internal auditors has a significant impact on fraud prevention, and the interaction between local culture and the role of internal audit has a significant influence on fraud prevention in local government. In general, the fraud prevention framework combines the dimensions of the role of internal auditors and local culture to create a system for preventing fraud and supporting the integrity and accountability of the organization. The analysis shows the R-Square value for the fraud prevention variable of 0.817, which indicates that the variables of the Role of Internal Audit and Local Culture have a significant influence on Fraud Prevention at 81.7%. These results indicate that the model has strong predictive power, and the rest has limitations in explaining 18.3% of the variance that can be explained by other variables that are not included in this research model.